XRF analysis of sediment core Co1412 in the Yana Highlands - Marlene M Baumer; Bernd Wagner; Hanno Meyer; Niklas Leicher; Matthias Lenz; Grigory B Fedorov; Luidmila A Pestryakova; Martin Melles (PANGAEA, 2021)
The sediment succession of Lake Emanda in the Yana Highlands was investigated to reconstruct the regional late Quaternary climate and environmental history. Hydro-acoustic data obtained during a field campaign in 2017 show laminated sediments in the north-western and deepest (up to ~15 m) part of the lake, where a ~6-m-long sediment core (Co1412, latitude 65°17.6490N, longitude 135°45.5540E) was retrieved. The sediment core was studied with a multi-proxy approach including sedimentological and geochemical analyses. The chronology of Co1412 is based on 14C AMS dating on plant fragments from the upper 4.65 m and by extrapolation, suggesting a basal age of c. 57 cal. ka BP. XRF analysis of sediment core Co1412: Mn/Fe=Manganese/Iron, K/Ti=Potassium/Titanium, Fe=Iron (cps) data of sediment Co1412 against composite depth (cm) and age (cal. a BP).